2022
DOI: 10.3390/ijerph19031542
|View full text |Cite
|
Sign up to set email alerts
|

Improved Monitoring and Assessment of Meteorological Drought Based on Multi-Source Fused Precipitation Data

Abstract: Meteorological drought, one of the most frequent climate-related disasters, causes great danger for human health and socioeconomic development. With an aim to improve the accuracy of meteorological drought monitoring, this study collected multi-source remotely-sensed precipitation products, i.e., the Tropical Rainfall Measuring Mission (TRMM), the Global Precipitation Measurement Mission (GPM), and Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), and compared their performance over Hube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In comparison, the TRMM fits the Z-I and Z-II drought assessments better, whereas the CHIRPS fits the Z-III drought analysis better [75,76]. Even at a 5 mm/d threshold, GPM worked best for numerical evaluation of precipitation and event detection [50].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In comparison, the TRMM fits the Z-I and Z-II drought assessments better, whereas the CHIRPS fits the Z-III drought analysis better [75,76]. Even at a 5 mm/d threshold, GPM worked best for numerical evaluation of precipitation and event detection [50].…”
Section: Discussionmentioning
confidence: 96%
“…In comparison, the TRMM fits the Z-I and Z-II drought assessments better, whereas the CHIRPS fits the Z-III drought analysis better [75,76]. Even at a 5 mm/d threshold, GPM worked best for numerical evaluation of precipitation and event detection [50]. The per cent agreement between precipitation from precipitation production and observed values from AWS showed that IMERGH registered the highest agreement per cent of 89.76, followed by 82.54 by TRMM.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Yan et al (2018) indicated that TRMM-3B43 has a good performance in representing the observed drought events over southwest China. In the other part of China, that is, over the plane land of Hubei Province, GPM precipitation data showed superior performance over CHIRPS and TRMM in representing historical droughts (Chen et al, 2022). Although some level of consistency between data products reported for GPCC, PERSIANN-CDR and CHIRPS (Wei et al, 2019) and between GPCC, CRU and the University of Delaware (Wei et al, 2020) precipitation products in representing drought events in most of China, GPCC outperformed the others and data products showed heterogeneity in representing drought events over the plateau area.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades and today, drought indices have been widely used as tools to assess and monitor drought conditions [82][83][84]. For assessing the most prominent indexes for each type of drought, Keyantash et al [85] used a weighted total of six evaluation criteria for the period 1980-2015, and Li et al [86] used two universally used meteorological drought indexes, the SPI and SPEI, to elucidate drought conditions across China.…”
Section: Drought Indices and Their Effectiveness In Monitoring Droughtmentioning
confidence: 99%